2016
DOI: 10.1038/pj.2016.102
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surface treatment on molecular reorientation of polymer-stabilized liquid crystals doped with oligothiophene

Abstract: Irradiation of dye-doped liquid crystals (LCs) with linearly polarized light leads to molecular reorientation, which manifests functional properties for various nonlinear optical (NLO) applications. Material designs with lower light intensity thresholds for molecular reorientation have been explored, and nematic LCs have been one of the most attractive choices because of the high NLO properties. Here we present a different approach to reduce light intensity for reorientation by modifying a substrate surface th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 39 publications
(48 reference statements)
0
11
0
Order By: Relevance
“…The difference in the threshold intensity, which reflects the sensitivity of molecular reorientation, is derived from the dielectric anisotropy of each sample. According to previous work, the threshold intensity is determined by a balance of four torques: opticalelectric torque, elastic torque, dye torque, and surface anchoring [15]. The increase in the optical-electric torque promotes the molecular reorientation.…”
Section: Samplementioning
confidence: 96%
See 2 more Smart Citations
“…The difference in the threshold intensity, which reflects the sensitivity of molecular reorientation, is derived from the dielectric anisotropy of each sample. According to previous work, the threshold intensity is determined by a balance of four torques: opticalelectric torque, elastic torque, dye torque, and surface anchoring [15]. The increase in the optical-electric torque promotes the molecular reorientation.…”
Section: Samplementioning
confidence: 96%
“…Instead of the anthraquinone dyes, Zhang et al reported the usage of oligothiophene dyes to enhance the sensitivity of the LC molecular reorientation [12]. To further decrease the light intensity required for the OFT in oligothiophene-doped LCs, various approaches focusing on the incident light, alignment processing, and materials have been proposed [13][14][15][16][17][18][19]. Recently, we focused on the material design and achieved the effective molecular reorientation by doping oligothiophene dyes with ester moieties [17,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A host nematic LC, 5CB (4-cyano-4′-pentyl biphenyl), was obtained from Merck Ltd., Tokyo, Japan. A4CB (4-[4-(4′-cyanobiphenyl)oxy]butyl acrylate) was mixed to host LC as a monoacrylate according to a previous report (A4CB:5CB = 10:90, molar ratio) [29]. The dye molecule, TR5 (5,5′′-Bis-(5-butyl-2-thienylethynyl)-2,2′:5′,2′′-ter thiophene) was synthesized as reported previously [30] and doped into the mixture of 5CB and A4CB at the concentration of 0.1 mol%.…”
Section: Methodsmentioning
confidence: 99%
“…The reorientation of LC molecules in optical field is enhanced by adding a small amount of absorbing dye molecules, which generally causes a photochemical reaction, to the LCs [15][16][17][18][19][20][21][22][23][24]. On the other hand, molecular reorientation without a photochemical reaction, termed photophysical process, has also been explored [25][26][27][28][29] because of exhibiting a well-defined threshold intensity of nonlinear molecular reorientation. We found that homeotropic-aligned LCs doped with an oligothiophene-dye (TR5) efficiently underwent the photophysical molecular reorientation with lower light intensity compared with previously reported dye-doped LCs [30].…”
Section: Introductionmentioning
confidence: 99%